SMOKING AND FLAP SURVIVAL: A COMPREHENSIVE SYSTEMATIC REVIEW - Nur Afiati, Shabrina; Marini, Dini (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Free flap reconstruction of complex and/or large wounds, whether traumatic, following cancer resection, or for other reconstructive needs has become a commonly accepted practice. Multiple different types of free flaps are utilized for varying needs based on the individual patient and the defect that requires coverage. active smokers who underwent a nonelective traumatic reconstruction with a perforator-based fasciocutaneous flap (anterolateral thigh [ALT] flap) will have a higher incidence of smoking-related complications compared to the use of a muscle-only flap. The aim: The aim of this study to show about smoking and flap survival. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 9 articles, whereas the results of our search on SagePub get 441 articles, on Google Scholar 4830 articles. Records remove before screening are 2771, so we get 2509 articles fos screening. After we screened based on record exclude, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Smoking decreases the alveolar oxygen pressure and subcutaneous wound tissue oxygen, and nicotine causes vasoconstriction, smokers are more likely to experience flap loss, hematoma, or fat necrosis than non-smokers. Preoperative and post-operative abstinence period of at least 1 week is necessary for smokers who undergo flap operations.